Records of the Charles Darwin Foundation : Galapagos National Park Guide Course - Charles Darwin Foundation; Galapagos National Park (1979)
This collection contains teaching materials by topic, course notebooks, handouts, lists, and other materials pertaining to the planning and teaching of the Guide courses by CDF staff and associates.
This collection was possibly compiled by Gayle Davis Merlen and was found in the Library bodega (store room) in 2008.
Spanish and English